Effect of industrial-grade heavy calcium carbonate powder on properties of white high-strength concrete. (16th May 2023) - Xia, Jingliang; Ke, Guoju; Leng, Faguang; Wang, Jing; Ren, Longfang; Liang, Haiyi
Highlights: With the increase of IHCP, fluidity of WHSC improved gradually. IHCP can significantly improve the whiteness of WHSC. IHCP can significantly improved the mechanical properties of WHSC at later age. WHSC containing 15% of 850 m 2 /kg IHCP has the highest cost performance. Abstract: In order to reduce costs and improve whiteness, industrial-grade heavy calcium carbonate powder (IHCP) is used in white high-strength concrete (WHSC), the influence of IHCP on the workability, whiteness, mechanical properties, chloride ion impermeability, carbonation resistance and shrinkage properties of WHSC is systematically studied, and then the related mechanism were explored by means of XRD, TG-DTG and MIP. The results reveal that IHCP can improve the workability, whiteness and mechanical properties of WHSC, and the more IHCP incorporated, the more obvious the improvement. While IHCP can reduce the impermeability and carbonation resistance of WHSC, and the more the IHCP incorporating, the more obvious the reduction. A low content of IHCP can effectively reduce the drying shrinkage of WHSC, and with the increase of IHCP content, the drying shrinkage of WHSC quickly increases to around without IHCP. Increasing the fineness of IHCP has limited effect on the performance of WHSC, but it will greatly increase the grinding cost of IHCP and the raw material cost of WHSC. WHSC containing 15% of 850 m 2 /kg IHCP has the highest cost performance.